Gerechtigkeit - Schlothfeldt, Stephan (Grundthemen Philosophie, 2012)
Justice has multiple facets. This volume examines retributive justice as well as transactional justice, and places special emphasis on distributive justice. The author establishes that an egalitarian understanding of distributive justice is superior to a model of justice based upon merit and need. The study shows that justice is undoubtedly an important category, one that is underdetermined in influential moral theories, but that justice cannot be the only standard for moral action. This volume in the Basic Topics in Philosophy series creates an important foundation for further discussion of the topic. Stephan Schlothfeldt, Universität Konstanz.